Genetic relatedness and virulence potential of Salmonella Schwarzengrund strains with or without an IncFIB-IncFIC(FII) fusion plasmid isolated from food and clinical sources - Felix, Monique A.; Sopovski, Danielle; Commichaux, Seth; Yoskowitz, Noah; Aljahdali, Nesreen H.; Grim, Christopher J.; Abbott, Carter N.; Carlton, Ashlyn; Han, Jing; Sanad, Yasser M.; Zhao, Shaohua; Wang, Xiong; et al. (Frontiers in Microbiology, 2024)
A total of 55 food and clinical S. Schwarzengrund isolates were assayed for plasmid content, among which an IncFIB-IncFIC(FII) fusion plasmid, conferring streptomycin resistance, was detected in 17 isolates. Amongst the 17 isolates, 9 were (nine from food and eight from clinical samples). fFood isolates isolates were primarily collected from poultry meat, while and 8 clinical isolates were collected from stool, urine, and blood. SNP -and cgMLST-based phylogenetic analyses showed that the isolates carrying the fusion plasmid formed a subclade indicating the plasmid was acquired and is now maintained by the lineage. Phylogenetic analysis of the plasmid suggesteds that it is derived from avian pathogenic plasmids and might confer an adaptive advantage to the S. Schwarzengrund isolates within birds. IncFIB-IncFIC(FII) fusion plasmids from all food and three clinical isolates were self-conjugative and successfully transferred into E. coli J53 by conjugation. Food and clinical isolates had similar virulome profiles and were able to invade human Caco-2 cells. Although the plasmid conferred streptomycin resistance to the S. Schwarzengrund isolates However, tthe IncFIB-IncFIC(FII) plasmid did not significantly add to their invasion and persistence potential in human Caco-2 cells.